Effects of Changes in ICU Bed Supply on ICU Utilization. Issue 7 (July 2019) - Barbash, Ian J.; Wallace, David J.; Kahn, Jeremy M.
Abstract : Background: The availability of intensive care unit (ICU) beds may influence the demand for critical care. Although small studies support a model of supply-induced demand in the ICU, there is a paucity of system-wide data. Objective: The objective of this study was to determine the relationship between ICU bed supply and ICU admission in United States hospitals. Research Design: Retrospective cohort study using all-payer inpatient records from Florida, Massachusetts, New Jersey, New York, and Washington from 2010 to 2012, linked to hospital data from Medicare's Healthcare Cost Reporting Information System. Subjects: Three patient groups with a low likelihood of benefiting from ICU admission—low severity patients with acute myocardial infarction and pulmonary embolism; and high severity patients with metastatic cancer at the end of life. Measures: We compared the risk-adjusted probability of ICU admission at hospitals that increased their ICU bed supply over time to matched hospitals that did not, using a difference-in-differences approach. Results: For patients with acute myocardial infarction, ICU supply increases were associated with an increase in the probability of ICU admission that diminished over time. For patients with pulmonary embolism, there was a trend toward an association between change in ICU supply and ICU admission that did not meet statistical significance. For patients with metastatic cancer, admission to hospitals with an increasing ICU supply was not associated with changes in the probability of ICU admission. Conclusions: Increases in ICU bed supply were associated with inconsistent changes in the probability of ICU admission that varied across patient subgroups. Abstract : Supplemental Digital Content is available in the text.